IDENTIFIKASI JAMUR PENYEBAB TINEA MANUUM PADA PEDAGANG IKAN DI PASAR KODIM KOTA PEKANBARU - Nurmi - Hasbi (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
Tinea mannum is fungal infection of the hands. These disease generally infected who worked at humanity and wet, such as fish traders. The available data about Tinea mannum in Indonesia are limited to case report. The purpose of this study to determinine the proportion of fungal infection in the hand of kodim market in Pekanbaru. This study is a descriptive study with purposive sampling method conducted involving 12 fish trader who suffer from fungal infected tinea mannum. The diagnosis is based microscopist and macroscopist. The microscopist examination using a 10 % KOH solution from hand’s skin and fungal culture in Saboraud Dextrose Agar. The results of this study showed all fish trader that infected of tinea mannum. Two groups of fungi were found, namely dermatophytes such as Trichophyton tonsurans as much as 5 fungi (6)% and non dermatophytes such as Aspergillus sp. as much as 6 fungi (30%), Yeast as much as 4 fungi (20%), Penicilium as much as 2 fungi (10%) and Trichoderma sp. ., Basidiobolus sp., Fusarium sp., Each as much as 1 fungi (5%).